A Remark on Social Semiotic Value of Personal Names in Selected Fiction Samples (American & British Studies Annual, 2009)
This paper is intended as a comment on an area of sociolinguistic studies that is closely related to the topic of personal and social identity. It is based on an analysis of corpus comprising three 20th century British novels and on a subsequent field research. The main  focus is on the symbolism that personal names and forms of address may carry in the current context of British society and, consequently, on the reflection of social hierarchy in general, and social class in particular on the way some personal names are perceived and used. From the theoretical perspective, this paper draws on Roger Fowler’s (1996) concept of text as discourse, and Mikhail Bakhtin’s (2008) heteroglossia, also incorporating the textual-functional perspective represented by the Prague Linguistic Circle as well as the work of M.A.K. Halliday. The ensuing analysis attempts to support the view that social indexicals as highly relevant agents in constructing our social reality can be successfully re-signified in reflexive acts of communication (cf Agha 2007).
Keywords: personal names; social semiotic value; personal and social identity; Mikhail Bakhtin; heteroglossia; Roger Fowler; text as discourse; textual-functional perspective; Prague Linguistic Circle; M.A.K. Halliday